Theoretical and methodological foundations of the HyFlex technology’s model - Аренова, Асыл; Жунусбекова, Азиза (Pedagogy and Psychology, 2022)
This article examined the problems of Hyflex technology, the methodology for creating, developing a model of a hybrid learning environment through this technology. Aspects of the mechanism of competitiveness of future teachers are presented, as well as the development of a concept, digital and scientific and methodological support for the organization of the educational process of this technology. Atheoretical analysis of past practices of combining offline and online teaching and learning, new mixed approaches to optimize costs and increase the availability and flexibility of students in educational institutions is given. Hybrid learning in modern education has also been considered in foreign science. Four main principles are considered that can be applied in the development of HyFlex technology. Examples of the application of this technology in foreign universities are given. In general, research is needed to complement the limited literature on HyFlex, as well as research on methods aimed at creating an optimal blended learning experience using this technology.